Studies of South India : an anthology of recent research and scholarship - Frykenberg, Robert Eric.; Kolenda, Pauline; Society for South India Studies (Madras : New Era Publications ; New Delhi : American Institute of Indian Studies, 1985)
Papers orginally presented at the Second South India Conference, organized by the Society for South India Studies, held at the University of Wisconsin, Madison, 1983.
Includes bibliographies and index.
Keywords: India, South -- Congresses